Synthesis of Superarmed Thioglycosides via the Ring Opening of 1,2-Orthoesters - Beato, Zoe; Zhu, Xiangming (Synlett, 2023)
Since the advent of the armed–disarmed strategy, thioglycosides have become essential tools in one-pot oligosaccharide synthesis. The continuum of glycosyl donor reactivity has since been expanded to include so-called ‘superarmed’ thioglycoside donors whose reactivity relies on more than just the inductive effects of protecting groups. Here we report a new method for the synthesis of superarmed thioglycosides via the ring opening of 1,2-orthoesters. This method ensures the necessary 1,2-trans stereochemistry, and importantly, makes use of trimethylsilyl thioethers as sulfur nucleophiles to avoid the use of unpleasant free thiols. Ten examples of ethyl and phenyl thioglycosides of mono- and disaccharides were synthesised from their orthoesters using tris(pentafluorophenyl)borane (BCF) as the Lewis acid promoter and were obtained in good yield and purity.
Keywords: thioglycoside; superarmed; BCF; orthoester; stereoselective